PENGEMBANGAN KAWASAN KAWAH IJEN SEBAGAI DESTINASI WISATA DI KABUPATEN BANYUWANGI - Bintang Madafuri; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2013)
ABSTRACT This study is about the development of Ijen Crater area as a tourism destination in Banyuwangi Regency. Ijen Crater is an active volcano, so it is always in the monitoring of volcanology center. When Ijen Crater conditions are not allowed to be visited, then the volcanology center immediately inform the natural resources conservation center in order to make a warning to tourists not to do climbing activity. Travelers who had already come disappointed with the prohibition. By the uncertain situation, there are need a strategy to make alternative activities. The new tourist activities carried out in the Ijen Crater area, so that tourists can still enjoy the travel without climbing Ijen Mountain. The whole existing condition of the potential in the ijen crater and surroundings area, it is important to analyze using indicators of special interest tourism concept. There are several potential was found, grouped into three categories that is, natural potential, artificial potential and cultural potential. The results of this analysis are used to determining some special interest tourism activities that appropriated and could be done in the Kawah Ijen as a tourism destination. Furthermore, indication of the programs and stages of development neeed to be designed using the three main steps that must be done, that is: short-term, medium-term and long-term development. Implementation of development carried out in accordance with the specified time. The development stages are expected could be monitoring the development of Ijen Crater area and also can make Ijen Crater area as a quality tourism destination.